Revolutionary Flipbook-Based Digital Comic: Changing Student Engagement in Learning - Elfina, Eni; Waskito, Waskito; Darni, Resmi; Maksum, Hasan; Novaliendry, Dony (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The development of digital technology has had a significant impact on various aspects of life, including education. The use of digital media in learning is a necessity to motivate and increase students' interest in learning. One form of digital media that attracts attention is flipbook-based comics. This research aims to develop digital flipbook-based comics as an innovative learning tool to increase students' interest in learning. This research uses a 4D development approach (Define, Design, Develop, and Disseminate) to design, develop, and implement digital flipbook-based comics as an innovative tool aimed at increasing students' interest in learning. This research also involved testing with a number of students to evaluate the effectiveness and attractiveness of digital flipbook-based comics as a learning tool. The data collected involves aspects of learning interest, understanding of the material, and student satisfaction with the use of digital flipbook-based comics. The research results show that the use of digital flipbook-based comics can significantly increase students' interest in learning. Students responded positively to the interactive and fun learning experience. Therefore, the development of digital flipbook-based comics is an innovative solution in increasing students' interest in learning in this digital era.